2020
DOI: 10.1186/s12912-020-00420-2
|View full text |Cite
|
Sign up to set email alerts
|

Nurses´ perceptions of automated dispensing cabinets – an observational study and an online survey

Abstract: Background: Thirty-two automated dispensing cabinets (ADCs) were introduced in May 2015 in Kuopio University Hospital, Finland. These medication distribution systems represent relatively new technology in Europe and are aimed at rationalising the medication process and improving patient safety. Nurses are the end-users of ADCs, and it is therefore important to survey their perceptions of ADCs. Our aim was to investigate nurses' perceptions of ADCs and the impacts of ADCs on nurses' work. Methods: The study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
1
3
0
5
Order By: Relevance
“…Overall, nursing and pharmacy assistant staff were satisfied with the system, in line with numerous recent studies (Ardern-Jones et al, 2009;Douglas et al, 2017;Metsämuuronen et al, 2020;Sirois et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
“…Overall, nursing and pharmacy assistant staff were satisfied with the system, in line with numerous recent studies (Ardern-Jones et al, 2009;Douglas et al, 2017;Metsämuuronen et al, 2020;Sirois et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
“…Unclear medication information, doses, and omitted verifications practices were found in our study, even though the study hospital partly used superior technology, such as automated dispensing cabinets (ADCs). In a previous study conducted in the same hospital, ACDs were found to make work easier, but some resistance to change was observed in the form of non-compliance to some instructions, for example, the barcode was not always used [24]. Following the guidelines and verification practices are important in ME prevention, but as found in earlier studies, more than half of the nurses often fail to follow guidelines during medication administration in Finland [25] and rule violations are common globally [26]; these are not only nursing problems.…”
Section: Discussionmentioning
confidence: 98%
“…Approximately 80% agreed that the ADM improved patients' safety. 118 As for the patients' experiences, Mertens et al 119 surveyed 62 patients to investigate the efficiency of an ADM. 119 Their result showed that most of the patients are satisfied with the ADM as it improved their ability to use medication appropriately. They stated that 40% of the patients agreed that the ADM prevented mistakes during their medication intake and also able to improve medication adherence.…”
Section: Survey and Feedbackmentioning
confidence: 99%